Please, Not Another Push to Get Tough on Student Retention - Norton, M. Scott (Planning & changing, 2011)
Standardized academic testing, under-performing schools, demands for high standards in America's schools and current levels of student dropouts have resulted in renewed calls for "getting tough on student retention." The push for student retention is demanded by school boards and others in spite of the overwhelming research evidence that student retention in-grade does not support the improvement of student academic performance or personal behavioral qualities. Social promotion whereby students move to the next grade level even though they have not mastered the academic requirements of a particular grade also is being questioned due to its unsatisfactory academic results. At this time in history, education researchers and practitioners do not have "best answers" to the on-going problem of student promotion. This article briefly discusses relevant research on student promotion and then gives primary attention to alternatives to student retention and social promotion. Emphasis is placed on the paramount importance of early identification of unsatisfactory learning performance and the continuous monitoring of student performance for each individual student. School organizational considerations such as new and/or expanded student learning strategies are presented. Re-engagement of students in the learning process, the need for teacher and administrator student advocacy, and efforts for preventing student failure are discussed. Strengthening parental involvement and recommendations for programs of professional development are considered from the perspective of fostering greater links to student achievement. (Contains 1 figure.)